Hubungan Pengetahuan Dan Dukungan Keluarga Terhadap Kepatuhan Minum Obat Pasien Dengan Hipertensi Pada Lansia Di Wilayah Kerja Puskesmas Kelurahan Baru Jakarta Timur - Okta Amalina Sabila; Saka Adhijaya Pendit; Teti Oktianingsih (Journal of Innovative and Creativity, 2026)
Hypertension in the elderly is still a health problem with high prevalence that requires compliance in treatment. Family knowledge and support are important factors that affect medication compliance. The research is to find out the relationship between knowledge and family support towards medication compliance in elderly patients with hypertension in the New Jakarta New Village Health Center Work Area. Uses observational analytical design ith a cross-sectional approach. A sampel of 74 respondents as taken using the purposive sampling technique. Using the Chi-square test. The results of the study showed that 79,7% had good knowledge, 47,3% had good family support, and 62,2% had compliance with medication compliance, there as a significant relationship between knowledge and between family support and medication compliance (p value a < 0,05). Family knowledge and support are significantly related to medication compliance in the elderly with hypertension.